1998
DOI: 10.1029/97gl03781
|View full text |Cite
|
Sign up to set email alerts
|

Self‐organization during reactive fluid flow in a porous medium

Abstract: Abstract. When a reactive fluid circulates inside a porous medium it can dissolve some minerals if equilibrium is not reached and modiy the porosity and permeability. The positive feedback between fluid transport and mineral dissolution lead to complex reaction front morphologies such as fingers. Our study is carried out with two objectives: l) to evaluate experimentally these processes at a decimeter scale, 2) to compare the experiment to a numerical model of water-rock interaction. The experiment consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…The effective specific surface area is not known and could vary by order of magnitudes. Renard et al [1998] reported a value of 350 m −1 and Bercovici et al [2001] argue that it can be as high as 10 6 m −1 . Ni and Beckermann [1991] show that the effective specific surface area is related to the porosity as A ∼ϕ(1 − ϕ).…”
Section: Model Descriptionmentioning
confidence: 99%
“…The effective specific surface area is not known and could vary by order of magnitudes. Renard et al [1998] reported a value of 350 m −1 and Bercovici et al [2001] argue that it can be as high as 10 6 m −1 . Ni and Beckermann [1991] show that the effective specific surface area is related to the porosity as A ∼ϕ(1 − ϕ).…”
Section: Model Descriptionmentioning
confidence: 99%
“…This occurs in viscous fingering if a less viscous fluid displaces a more viscous one [1]. Fingering can also result from a change in permeability in a porous medium as in reactive dissolution instabilities [2][3][4][5][6][7][8][9][10]. In these cases, the invading fluid contains chemicals which dissolve the solid matrix of the porous medium, leading to a related increase in porosity behind the reaction front.…”
mentioning
confidence: 99%
“…The experiments and nonlinear simulations of a RDC model give results in good agreement. We emphasize that the modeling of this precipitation-induced fingering is analogous to that of reactive viscous fingering [20,21,[24][25][26][27] and dissolution-driven fingering [2][3][4][5][6][7][8][9][10] with nonmonotonic profiles. The present study paves the way to future detailed analysis of the influence of precipitation reactions on the stability of displacement processes in porous media.…”
mentioning
confidence: 99%
“…Nevertheless, the mechanism of the preferential flow caused by NAPL dissolution fingering is different from that caused by medium heterogeneity. From the physical point of view, the former is considered as an emerging phenomenon due to the instability of a nonlinear system (Chadam et al, 1986(Chadam et al, , 1988Liu, 2002, 2004;Chen et al, 2009;Ortoleva et al, 1987;Renard et al, 1998;Zhao et al, 2008aZhao et al, , 2008bZhao et al, , 2008cZhao et al, , 2009Zhao et al, , 2010aZhao et al, , 2010b, while the latter is considered as the conventional phenomenon of a nonlinear system (Alt-Epping and Smith, 2001;Maji and Sudicky, 2008;Ormond and Ortoleva, 2000;Raffensperger and Garven, 1995;Schafer et al, 1998;Lasaga, 1990, 1994;Yeh and Tripathi, 1991).…”
Section: Introductionmentioning
confidence: 98%